Synthesis of chromium substituted nano particles of cobalt zinc ferrites by coprecipitation - Sharma, R. K.; Suwalka, O.; Lakshmi, N.; Venugopalan, K.; Banerjee, Abhik; Joy, Pattayil Alias (Materials Letters, 2005)
Nano particles of chromium substituted cobalt zinc ferrite have been synthesized by a chemical co-precipitation method. X-ray diffraction studies of the nano particles of CrxCo0.5-xZn0.5Fe2O4 (x = 0.1 to 0.5) heat-treated at 300 degrees C show that the particle sizes are in the range of 2 to 7 nm. Room temperature Fe-57 Mossbauer spectra of all the samples show only two doublets, confirming the presence of superparamagnetic relaxation in the nano particles. An exponential decrease in the superparamagnetic blocking temperature, with increasing chromium concentration, is observed for these samples. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Co0.5Zn0.5Fe2O4; Mossbauer spectroscopy; nano materials